School-wide mediated prosocial development: Applying a sociocultural understanding to inclusive practice and character education. (1st October 2016) - White, Robert; Shin, Tae Seob
Abstract : The issue of inclusive practice, particularly as it pertains to how school staff address antisocial behavior to improve learning and life outcomes for children has become a primary topic of discussion among educational stakeholders. Within an action research framework, this investigation used a mixed-method multiple case study approach to investigate what impact character education has on school climate and pupil behavior within five primary schools in England. Data were collected using interviews, observations, and archived records. All data-sets suggest that a multicomponent socioculturally inspired program can have positive effects on teacher talk, student on-task behavior, and decrease disruptive incidences during class and office referrals for antisocial behavior. Moreover, according to participant reports, the findings indicate that there is a positive effect on the school's ability to meet the social, emotional, and cognitive needs of pupils within a multicultural setting following the implementation of a whole-school character education program.